2022
DOI: 10.7150/ijbs.65457
|View full text |Cite
|
Sign up to set email alerts
|

Role of RHO family interacting cell polarization regulators (RIPORs) in health and disease: Recent advances and prospects

Abstract: The RHO GTPase family has been suggested to play critical roles in cell growth, migration, and polarization. Regulators and effectors of RHO GTPases have been extensively explored in recent years. However, little attention has been given to RHO family interacting cell polarization regulators (RIPORs), a recently discovered protein family of RHO regulators. RIPOR proteins, namely, RIPOR1-3, bind directly to RHO proteins (A, B and C) via a RHO-binding motif and exert suppressive effects on RHO activity, thereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…High expression of the RIPOR2 gene in hair follicle cells has been associated with the regulation of hair growth, which has been confirmed by the presence of polymorphisms that cause hair loss in humans [ 26 ]. Disorders in the RIPOR2 gene are also accompanied by the development of oncological diseases [ 27 ]. The effect of the gene on productivity in animals has not been studied, but the described effects of mutations in it allowed us to consider it as a potential candidate gene for further study.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of the RIPOR2 gene in hair follicle cells has been associated with the regulation of hair growth, which has been confirmed by the presence of polymorphisms that cause hair loss in humans [ 26 ]. Disorders in the RIPOR2 gene are also accompanied by the development of oncological diseases [ 27 ]. The effect of the gene on productivity in animals has not been studied, but the described effects of mutations in it allowed us to consider it as a potential candidate gene for further study.…”
Section: Discussionmentioning
confidence: 99%
“…The robust expression of fam65c gene, a member of the Rho family-interacting cell polarization regulator (RIPORs), was probably linked to the migration of xanthophores/erythrophores. This gene plays an essential role in the modulation of the cell differentiation, migration, adhesion, polarization and organelle tra cking [39,40], apart from immunity [41]. Several common DEGs discovered in xanthophores/ erythrophores coloration in shes [18,42], such as the tgm, clbn, thbs and hoax, were also found in the RMAvsRMJ but their roles in pigmentation have remained unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Actin reorganization is regulated by cofilin and LIMK, which are downstream molecules of RhoA, and their phosphorylation is regulated by RhoA activation [ 35 ]. The regulation between autophagy and the RHO family has double-planedness in some studies [ 36 , 37 ]. Herein, we found that both Siglec-15 silencing and Beclin-1 depletion could decrease RhoA activation and lessen the formation of lamellipodial protrusions in the submembranous area in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%